Trichohepatoenteric syndrome: A rare mutation in SKIV2L gene in the first Balkan reported case. (October 2018) - Xinias, Ioannis; Mavroudi, Antigoni; Mouselimis, Dimitrios; Tsarouchas, Anastasios; Vasilaki, Konstantina; Roilides, Ioannis; Lacaille, Florence; Giouleme, Olga
Trichohepatoenteric syndrome or syndromic diarrhea is a rare and severe Mendelian autosomal recessive syndrome characterized by intractable diarrhea, facial and hair abnormalities, liver dysfunction, immunodeficiency and failure to thrive. It has been associated with mutations in TTC37 and SKIV2L genes, which encode proteins of the SKI complex that contributes to the cytosolic degradation of the messenger RNA by the cell's exosome. We report a case of a male infant who suffered from typical symptoms and signs of trichohepatoenteric syndrome without immunodeficiency. The patient's genetic testing showed a very rare mutation in SKIV2L gene's 25 exons (p.Glu1038 fs*7 (c.3112_3140del)). Even though our patient was provided with total parenteral nutrition from birth, the child's death in the third year of age highlights the severity of the disease and the poor prognosis of this particular type of genetic predisposition.